Analisis Prediksi Potensi Kebangkrutan dengan Menggunakan Model Springate Studi pada Bank Muamalat Indonesia Periode 2020-2024 - Wiya Wahyuni; Muhammad Masruron; Muh.Khairul Fatihin (Jurnal Literasi Akuntansi, 2025)
Purpose: This study aims to analyze the bankruptcy prediction of Bank Muamalat Indonesia using the Springate Model as a financial health assessment tool. Predicting bankruptcy is crucial for management to anticipate potential financial distress and maintain the bank’s long-term financial stability. Method: The research adopts a quantitative descriptive approach using secondary time series data obtained from the annual financial reports of Bank Muamalat Indonesia. The population includes all financial statements from 1992 to 2024, while the sample was selected purposively, focusing on the financial reports for the 2020–2024 period. The data were analyzed using the Springate S-Score Model, which incorporates four key financial ratios: working capital to total assets, earnings before interest and taxes to total assets, earnings before taxes to current liabilities, and sales to total assets. Finding: The analysis results show that the S-Score values of Bank Muamalat Indonesia during 2020–2024 consistently remained above the cut-off point of 0.862. This indicates that the bank’s financial condition was generally healthy and not at risk of bankruptcy. Despite minor fluctuations in operating profits, the steady increase in total assets each year reflects the bank’s strong ability to maintain liquidity and operational efficiency. Novelty: This study contributes to the existing literature by applying the Springate Model within the context of Islamic banking in Indonesia. It provides an empirical overview of Bank Muamalat Indonesia’s financial resilience during the post-pandemic economic recovery period, highlighting the model’s relevance in assessing financial stability in Islamic financial institutions.